Intelligent mobile projects with tensorflow : build 10+ artificial intelligence apps using TensorFlow Mobile and Lite for iOS, Android, and Raspberry PI /: build 10+ artificial intelligence apps using TensorFlow Mobile and Lite for iOS, Android, and Raspberry PI. (2018) - Tang, Jeff
No abstract available